Monoclonal antibodies for chronic migraine and medication overuse headache: A real-world study - Krymchantowski, Abouch V.; Jevoux, Carla; Krymchantowski, Ana Gabriela; Silva-Néto, Raimundo Pereira (Frontiers in Neurology, 2023)
Background: Medication-overuse headache is highly prevalent in tertiary care centers. It may be cause or consequence of the overuse of symptomatic medications for migraine attacks. Objective: We aimed to compare the efficacy of anti-CGRP monoclonal antibodies (mAbs) added to conventional pharmacological treatment in patients with chronic migraine (CM) and medication overuse headache (MOH). Methods: A cross-sectional, prospective, randomized, open study with real-world comparison groups was carried out. The sample consisted of 200 consecutive patients with CM and MOH, who received the same approach to withdraw overused medications, start prevention and adding or not a mAb. Results: A total of 172 patients (126 women and 46 men) were included in the study and divided into two groups: group 1 consisting of 58 patients (control) and group 2 of 114 patients who used mAbs added to conventional pharmacological agents. The mean age was 44.1±13.6 years, ranging from 18 to 78 years. In the three months follow-up after starting treatment both groups presented reduction, but those with monoclonal antibodies had a significant higher reduction in the number of headache days and symptomatic medication intake when compared to the control (p<0.0001). Conclusions: The addition of an anti-CGRP monoclonal antibody to the treatment of chronic migraineurs and medication overuse headache may result in decreasing headache frequency and symptomatic medication use when compared to conventional treatment with drugs.